Effect of Grape Seed Extracts on the Physicochemical and Sensory Properties of Corn Chips during Storage - Rababah, Taha M.; Yucel, Sevil; Ereifej, Khalil I.; Alhamad, Mohammad N.; Al-Mahasneh, Majdi A.; Yang, Wade; Muhammad, Al-u'datt H.; Ismaeal, Khalid (WILEY, 2011)
This study evaluated the effectiveness of grape seed extracts (GSE) on lipid oxidation of corn chips stored for 90 days in comparison to tert-butylhydroxytoluene (BHT). Proximate chemical analysis results showed that corn chips contained low moisture contents (less than 2%) and also that no significant differences were found in the dry matter values in ash, fat, protein, and fiber. Antioxidant activity of the GSE measured by an oxidative stability instrument ranged from 1.6 to 9.3 h of induction time, while BHT prevented oxidation by 18.8 h. GSE (800 ppm) increased the redness and decreased the brightness and yellowness of the corn chip samples, whereas no significant differences were observed for other concentrations of the GSE compared to the control. The peroxide values (PV) for the control and the lower concentration (200 ppm) of GSE increased from 4.5 to 32.7 mequiv/kg, and from 4.4 to18.7 mequiv/kg, respectively, while no increase in PV was found for the higher level (400 and 800 ppm) of GSE or BHT. These changes were observed after 90 days of storage. Descriptive and consumer results showed that the control and the low concentration of GSE were associated with an increase in rancidity and the appearance of off-flavor, while no noticeable increase in either rancidity or off-flavor was observed when using a higher concentration of GSE or BHT. GSE has great potential for use as a natural antioxidant to preserve the extruded corn chips.
Keywords: Lipid oxidation; Sensory; Antioxidants; ANTIOXIDANT ACTIVITIES; TOTAL PHENOLICS; BLACK TEA; MEAT; Chemistry; Food Science & Technology